Sequential water balance and its respective rainfall erosion in the municipality of Amparo de São Francisco - SE, Brazil (Research, Society and Development, 2021)
The objective is to carry out the calculation of the sequential water balance between the years 1963 - 2019 for Amparo de São Francisco - SE, with the purpose of verifying the variability of the erosive index of the studied area. The monthly and annual rainfall data were acquired from the database of the Northeast Development Superintendence and from the Technical Assistance and Rural Extension Company of the state of Sergipe, for the period mentioned above. The thermal data were estimated by the Estima T software. The applied methodology was developed by Thornthwaite. The erosive rates flowed between 7500 MJ/mm/ha/year at 28000 MJ/mm/ha/year, it is noteworthy that these indexes are interconnected to rainfall fluctuations that registered with great magnitudes and in a short time interval. The results of the water balance showed that the local conditions contained by the high rainfall index can cause high erosivity and show us that this methodology should be used for future studies involving the same theme of initiative of this study under discussion.